1997
DOI: 10.1108/13527599710190939
|View full text |Cite
|
Sign up to set email alerts
|

Erratum

Abstract: This article has been withdrawn as it was published elsewhere and accidentally duplicated. The original article can be seen here: 10.1108/02621719510078966. When citing the article, please cite: P. Mazany, S. Francis, P. Sumich, (1995), “Evaluating the effectiveness of an outdoor workshop for team building in an MBA programme”, Journal of Management Development, Vol. 14 Iss: 3, pp. 50 - 68.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This specific form of OAE, often termed “outdoor-centered training,” is different from other types of outdoor adventure activities such as wilderness expeditions (e.g., sailing and backpacking), which tend to be longer and have less structured outcomes (Mazany, Francis, & Sumich, 1997). In comparison, the shorter, outdoor-centered form of OAE is also more easily embedded into degree courses with large student numbers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This specific form of OAE, often termed “outdoor-centered training,” is different from other types of outdoor adventure activities such as wilderness expeditions (e.g., sailing and backpacking), which tend to be longer and have less structured outcomes (Mazany, Francis, & Sumich, 1997). In comparison, the shorter, outdoor-centered form of OAE is also more easily embedded into degree courses with large student numbers.…”
mentioning
confidence: 99%
“…Quantitative studies have also explored students’ reaction and learning during OAE. For example, a group of business students completed a bespoke questionnaire before and after a 4-day OAE course (Mazany et al, 1997). Although significant increases were measured in groupwork skills such as decision making, inclusion of team members, communication, cohesion, time management, planning, and problem solving (Level 2), the authors suggested that further research was needed using more dependable measures of groupwork.…”
mentioning
confidence: 99%